Cultural dimensions and entrepreneurial performance interaction in small and medium enterprises in Zimbabwe (2019)
Although culture is generally considered as a determinant of entrepreneurship, consensus is generally lacking on the precise influence of this variable on entrepreneurial performance in emerging economies. Using a quantitative approach, this confirmatory, cross-disciplinary study sought to investigate the effect of cultural dimensions, on entrepreneurial performance of among Small and Medium Enterprises in Zimbabwe. The independent variables were derived primarily from Hofstede's cultural dimensions and a total of 250 questionnaires were distributed to Small and Medium Enterprises in Zimbabwe. The research adopted a multisector approach and respondents were drawn from the ten provinces of Zimbabwe. To confirm the existence of a relationship between cultural dimensions and entrepreneurial performance, structural equation modeling, a confirmatory, multivariate technique, was employed, starting with representing the causal relationships between these variables in a pictorial form. The findings from this research are consistent with the propositions that the dimensions of culture have a significant and positive influence on entrepreneurial performance. The results also affirm the findings of previous studies that have been carried out on the influence of culture on entrepreneurial performance. Over and above the generic dimensions of culture, this study adds the mediating role of the propensity to act and perceived feasibility.